In a New Connected World - Cipolla, Costantino; Siino, Antonia Roberta (Italian Sociological Review, 2017)
In the last decades, societies had to face great social changes. In the current globalised world, individuals are always more connected one to each other and the social network in which they are inserted have a deep influence on them. At the same time, ancient phenomena like the terroristic one have shown great capabilities in adapting to them. Even if secular and religious terroristic groups are not so different as they could appear, different explanations for a different type of terrorism have been defined. The great challenge of our days is to understand the real meanings of the change occurred; above all, a new form of relations and interrelations must be considered. Indeed, all social transformation concerning individuals and their social networks are reflected by larger phenomena. In this perspective, the globalisation process, the spread of the digital era and the spread of Information Communicational Technologies have had a great impact on the social structure of current communities. Indeed, the easy access to new technologies and their potentialities are key elements in the evolution of terroristic organisations. The aim of this article is to offer an overview on this subject inserted in the international context, underlying the deep change occurred from an organised relation to a connected organisation of actors.